2020
DOI: 10.1142/s1793604720510418
|View full text |Cite
|
Sign up to set email alerts
|

Improved solid electrolyte interphase and Li-storage performance of Si/graphite anode with ethylene sulfate as electrolyte additive

Abstract: Silicon/graphite composite anodes have drawn extensive attention in the field of power Li-ion batteries for application in electric vehicles because of their much higher capacity than that of traditional graphite anodes. In this work, ethylene sulfate (1,3,2-dioxathiolane-2,2-dioxide, DTD) is investigated as an electrolyte additive to improve the Li-storage performance of silicon/graphite composite anode. The electrochemical behavior of silicon/graphite anode including cyclic voltammogram, discharge/charge per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Interestingly, in addition to graphite negative electrode, DTD endows high compatibility toward silicon oxide (SiO x )-based negative electrode. 110,111 Zheng et al 110 reported that the DTD-containing electrolyte, that is, 1.0 M LiPF 6 -EC/EMC/DMC/fluoroethylene carbonate (FEC) (1/1/1/0.1, by vol) + 3 wt% DTD, shows higher initial Coulombic efficiency of 83.7% from 79.4% (the control group) and high cycling performance (the LijjSiO x cells exhibits good cycle stability after 500 cycles with 80% capacity retention). Li et al 111 demonstrated that the addition of 1.5 wt% DTD in a well-formulated baseline electrolyte (i.e., 1.0 M LiPF 6 -EC/EMC/DEC [3:5:2, by wt] + 0.5 wt% lithium difluoro(oxalato)borate [LiDFOB] + 2 wt% LiFSI + 2 wt% FEC + 1 wt% PS) results in a clear improvement in the cyclability of SiO xbased compositejjLiNi 0.8 Mn 0.1 Co 0.1 O 2 pouch cell (e.g., ca.…”
Section: 3-propane Sultonementioning
confidence: 99%
“…Interestingly, in addition to graphite negative electrode, DTD endows high compatibility toward silicon oxide (SiO x )-based negative electrode. 110,111 Zheng et al 110 reported that the DTD-containing electrolyte, that is, 1.0 M LiPF 6 -EC/EMC/DMC/fluoroethylene carbonate (FEC) (1/1/1/0.1, by vol) + 3 wt% DTD, shows higher initial Coulombic efficiency of 83.7% from 79.4% (the control group) and high cycling performance (the LijjSiO x cells exhibits good cycle stability after 500 cycles with 80% capacity retention). Li et al 111 demonstrated that the addition of 1.5 wt% DTD in a well-formulated baseline electrolyte (i.e., 1.0 M LiPF 6 -EC/EMC/DEC [3:5:2, by wt] + 0.5 wt% lithium difluoro(oxalato)borate [LiDFOB] + 2 wt% LiFSI + 2 wt% FEC + 1 wt% PS) results in a clear improvement in the cyclability of SiO xbased compositejjLiNi 0.8 Mn 0.1 Co 0.1 O 2 pouch cell (e.g., ca.…”
Section: 3-propane Sultonementioning
confidence: 99%
“…and higher viscosity, leading to electrolyte deterioration and gas production (Figure 1a). [24,25] To conquer the above issues, several LiNO 3containing additives have been successfully developed recently inspired by the sustained-release strategy, and their impressive performances demonstrate the great application potential of this method. [26,27] Therefore, optimizing the overall performance and cost of additives designed based on this strategy is of great research significance.Herein, we adopt cheap, environment-friendly CaCO 3 nanoparticles (40-80 nm) as a novel solid additive for LMBs.…”
mentioning
confidence: 99%
“…For the sake of completeness, reports where FEC is utilized as an electrolyte additive can be found in references [ 45–47,51–55,60–62,67,69,73,75–77,92–125 ] and reports utilizing VC as electrolyte additive can be found in references. [ 40,45,47–49,69,71,73,75–77,98,99,102–104,106,115,119,122,123,126–132 ]…”
Section: Electrolyte Interfacing Si‐based Electrodementioning
confidence: 99%
“…XPS analysis suggested the formation of a thinner SEI containing sulfate and sulfonate species. [ 93 ] An et al. studied a number of different additives in high capacity NMC811||SiO x cells.…”
Section: Electrolyte Interfacing Si‐based Electrodementioning
confidence: 99%
See 1 more Smart Citation